Non-steroidal anti-inflammatory drugs may modulate the protease activity of Candida albicans - Carvalho, Alessandra P.; Gursky, Lauren C.; Rosa, Rosimeire T.; Rymovicz, Alinne U. M.; Campelo, Patricia M. S.; Gregio, Ana Maria T.; Koga-Ito, Cristiane Y. [UNESP]; Samaranayake, Lakshman P.; Rosa, Edvaldo A. R. (Academic Press Ltd Elsevier B.V. Ltd, 2010)
The phenotypic pressure exerted by non-steroidal anti-inflammatory drugs (NSAIDs) on autochthonous and pathogenic microbiota remains sparsely known. In this study, we investigated if some NSAIDs increment or diminish the secretion of aspartyl-proteases (Sap) by Candida albicans grown under different phenotypes and oxygen availability using a set of SAP knock-out mutants and other set for genes (EFG1 and CPH1) that codify transcription factors involved in filamentation and protease secretion. Preconditioned cells were grown under planktonic and biofilm phenotypes, in normoxia and anoxia, in the presence of plasma concentrations of acetylsalicylic acid, diclofenac, indomethacin, nimesulide, piroxicam, ibuprofen, and acetaminophen. For diclofenac, indomethacin, nimesulide, and piroxicam the secretion rates of Sap by SAP1-6, EFG1. and CPH1 mutants were similar or, even, inferior to parental wildtype strain. This suggests that neither Sap 1-6 isoenzymes nor Efg1/Cph1 pathways may be entirely responsible for protease release when exposed to these NSAIDs. Ibuprofen and acetaminophen enhanced Sap secretion rates in three environmental conditions (normoxic biofilm, normoxic planktonic and anoxic planktonic). In other hand, aspirin seems to reduce the Sap-related pathogenic behavior of candidal biofilms. Modulation of Sap activity may occur according to candidal phenotypic state, oxygen availability, and type of NSAID to which the cells are exposed. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Candida albicans; NSAID; Protease; Biofilm; Normoxia; Anoxia